Annual Innovahub Meeting: Exchange of results and learnings between national and local agrifood actors in Guatemala and Honduras - Loon, Jelle van; Leal Gonzalez, Abel Jaime; García Santiago, Jorge O.; Martínez, Jesús David; Obando, Diego; Borrayo, Andrea; Martínez, Oscar; Jiménez, Daniel (Bioversity International and the International Center for Tropical Agriculture, 2023)
Under the Latin American Regional initiative AgriLAC Resiliente, the establishment of Innovahubs in Guatemala and Honduras has been a pivotal focus. At year end, in each country intensive stakeholders' meetings were organized at the subnational level to foster participatory discussions and delineate key aspects on how to consolidate and mature the Innovahubs and its core activities. Rooted in a hub model approach, the Innovahubs aim to catalyze innovation by facilitating spaces for collaborative learning, adapting to local contexts, and promoting interactive knowledge acquisition. November 2023 witnessed therefore the second execution of these meetings in varied locations across Guatemala and Honduras, employing diverse activities like interviews, round tables and plenary discussion as well as interactive sessions. These exercises aimed to discern local needs, research priorities, and pave the way for future action cycles. A hallmark approach is as always to foster dialogues with local stakeholders, understanding their perspectives, and forging consensus-driven strategies. In 2023, the meetings differed slightly from the 2022 exercise, as this year for the first-time field results could be presented and instead of having a separate meeting pet Innovahub, key Innovahub members from both Innovahub were invited to share their experiences among themselves in a common place. Guatemala emphasized sharing current outcomes, whereas Honduras accentuated synergies and mutual objectives. Both countries outlined action plans for 2024, targeting pivotal challenges such as poverty, migration, gender, climate change, and food security. The Guatemala hubmeeting on November 21 convened 25 institutions, focusing on fortifying the positive impacts of the Innovahubs in the region. Similarly, on November 23, 14 institutions congregated in Honduras, emphasizing advancements in innovation network management, and strategizing for further development of the Innovahubs. Reflecting on a year's journey, the collaborative endeavors under the AgriLAC initiative have illuminated clearer pathways in activities, products, and overarching objectives. In Guatemala, capacity building efforts spanning agronomic expertise to market linkages has been underlined as crucial, including an emphasis on training targeting community leaders and sustainable agriculture technicians. Concurrently, in Honduras, significant strides have been made, especially in integrating partners across regions and emphasizing gender inclusivity. The overarching vision remains to foster sustainable expansion, transcending traditional paradigms, and laying a robust foundation for the Resilient AgriLAC initiative's third-year blueprint in 2024.